2022
DOI: 10.1002/jmri.28364
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling‐Based MRI Estimation of Penumbral Tissue in Acute Ischemic Stroke

Abstract: Background: Arterial spin labeling (ASL) has shown potential for the assessment of penumbral tissue in patients with acute ischemic stroke (AIS). The postlabeling delay (PLD) parameter is sensitive to arterial transit delays and influences cerebral blood flow measurements. Purpose: To assess the impact of ASL acquisition at different PLDs for penumbral tissue quantification and to compare their performance regarding assisting patient selection for endovascular treatment with dynamic susceptibility contrast MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Most studies suggest that ASL can be used to assess the presence and size of ischemic lesions, but that it overestimates the lesion size, especially when shorter PLDs are used (e.g. 32 ). The lesion size can be compared to diffusion imaging measures of ischemic core size to determine a mismatch.…”
Section: Practical Acquisition and Post-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies suggest that ASL can be used to assess the presence and size of ischemic lesions, but that it overestimates the lesion size, especially when shorter PLDs are used (e.g. 32 ). The lesion size can be compared to diffusion imaging measures of ischemic core size to determine a mismatch.…”
Section: Practical Acquisition and Post-processingmentioning
confidence: 99%
“…Most reported ASL studies in acute stroke are single center studies with less than 100 subjects and limited randomization to assess the impact of ASL on diagnosis and outcomes. Two notable exceptions are a multi-site comparison of lesion volumes between ASL and contrast 32 and a multi-site comparison of thrombectomy outcomes using ASL and CT perfusion for treatment criteria. 36 The second study showed statistically identical outcomes, though with a trend towards higher complications using ASL.…”
Section: Practical Acquisition and Post-processingmentioning
confidence: 99%
“…The study by Lyu et al 8 in this issue addresses the existing challenges of ASL in AIS. Unlike previous studies focusing on thresholds for severe hypoperfusion segmentation, the authors investigated the effects of PLD of ASL perfusion on the estimation of penumbra in AIS.…”
mentioning
confidence: 99%